2023
DOI: 10.18502/ijrm.v21i2.12803
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glibenclamide and troxerutin on the sperm parameters and histopathological changes of testis in streptozotocin-induced diabetic male rats: An experimental study

Abstract: Background: Oxidative stress is a major contributor to diabetes mellitus (DM), which leads to testicular damage and infertility. Objective: The aim of this study was to investigate the effects of glibenclamide (GL) as a chemical medicine and troxerutin (TR) as an herbal agent on sperm parameters and histopathological changes of testis in diabetic male rats. Materials and Methods: Forty male Wistar rats (230-260 gr) were randomly divided into 5 groups (n = 8/each), including control, diabetic (D), GL, TR,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
(31 reference statements)
1
0
0
Order By: Relevance
“…Several earlier studies have suggested potential interventions to guard against type 1 diabetes-induced testicular atrophy, including specific medications, antioxidant-rich diets, and dietary supplements [30,31]. Our findings support these previous studies and suggest that the antioxidant activity of 4HR may mediate its protective effects on testicular function in the context of DM [19].…”
Section: Discussionsupporting
confidence: 90%
“…Several earlier studies have suggested potential interventions to guard against type 1 diabetes-induced testicular atrophy, including specific medications, antioxidant-rich diets, and dietary supplements [30,31]. Our findings support these previous studies and suggest that the antioxidant activity of 4HR may mediate its protective effects on testicular function in the context of DM [19].…”
Section: Discussionsupporting
confidence: 90%
“…Several antidiabetic agents are available in the market to help reduce the effect of DM, including metformin. Metformin is one of the commonly consumed antidiabetic agents [11]. However, its long-term use risks the organ system in the body.…”
Section: Introduction mentioning
confidence: 99%